Early Visual Processing Is Associated With Social Cognitive Performance in Recent-Onset Schizophrenia - McCleery, Amanda; Wynn, Jonathan K.; Lee, Junghee; Reavis, Eric A.; Ventura, Joseph; Subotnik, Kenneth L.; Green, Michael F.; Nuechterlein, Keith H. (Frontiers in Psychiatry, 2020)
Background: Early-stage visual processing deficits are evident in chronic schizophrenia. Consistent with a cascade model of information processing, whereby early perceptual processes have downstream effects on higher-order cognition, impaired visual processing is associated with deficits in social cognition in this clinical population. However, the nature of this relationship in the early phase of illness is unknown. Here, we present data from a study of early visual processing and social cognitive performance in recent-onset schizophrenia (ROSz). Method: Thirty-two people with ROSz and 20 healthy controls (HC) completed a visual backward masking task using stimuli of real world objects (Object Masking) to assess early-stage (i.e., 0 - 125 ms post-stimulus onset) visual processing. Subjects also completed two tasks of social cognition, one assessing relatively low-level processes of emotion identification (Emotion Biological Motion, EmoBio), and another assessing more complex, higher-order theory of mind abilities (The Awareness of Social Inference Test, TASIT). Group differences were tested with repeated measures ANOVAs and t-tests. Bivariate correlations tested the strength of associations between early-stage visual processing and social cognitive performance in ROSz. Results: For Object Masking, the mask interfered with object identification over a longer interval for ROSz than for HC [F (3.01, 150.57) = 3.04, p = 0.03]. ROSz were less accurate on the EmoBio task [t (50) = -3.36, p = 0.001] and on the TASIT compared to HC [F (1, 50) = 38.37, p < 0.001]. For the TASIT ROSz were disproportionately impaired on items assessing sarcasm detection [F (1, 50) = 4.30, p = 0.04]. In ROSz, better Object Masking performance was associated with better social cognitive performance [r EmoBio = 0.45, p < 0.01; r TASIT = 0.41, p < 0.02]. Conclusion: Early-stage visual processing, low-level social cognition, and high-level social cognition were all significantly impaired in ROSz. Early-stage visual processing was associated with performance on the social cognitive tasks in ROSz, consistent with a cascade model of information processing. These data suggest that interventions directed at early visual processing may yield downstream effects on social cognitive processes.